1986
DOI: 10.1093/ije/15.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cancer in the United States: Trends in Incidence and Mortality

Abstract: The patterns of incidence and mortality of testicular cancer in the United States indicate substantial differences by age, race, time period, and geographical region. An epidemic increase over time in the risk of testicular cancer is noted for young men aged 15-44, with the most recent birth cohorts showing the greatest rate of increase. Indeed, some of the evidence suggests the possibility of two separate increases, one apparent from at least the late 1930's through the late 1950's and the second appearing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(34 citation statements)
references
References 0 publications
3
29
2
Order By: Relevance
“…We found an increasing risk for seminoma with increasing milk fat intake and an even stronger association between galactose consumption and seminoma especially in the younger men ages 15 to 34 years. Although several epidemiologic studies indicate that risk factors for seminoma and nonseminoma may differ (13,16,(24)(25)(26)(27)(28)(29), it is unclear whether the specificity of the observed effects in our study (no association with nonseminoma risk) is causal or not because the subgroup of nonseminoma patients was small, resulting in imprecise effect estimates. In their registry-based prevalence case-control study, Davies et al (6) found that the RR per 1/4 pint of milk per day (i.e., f120 mL per day) at age 17 years was 1.39 (95% CI, 1.19-1.63).…”
Section: Discussioncontrasting
confidence: 56%
“…We found an increasing risk for seminoma with increasing milk fat intake and an even stronger association between galactose consumption and seminoma especially in the younger men ages 15 to 34 years. Although several epidemiologic studies indicate that risk factors for seminoma and nonseminoma may differ (13,16,(24)(25)(26)(27)(28)(29), it is unclear whether the specificity of the observed effects in our study (no association with nonseminoma risk) is causal or not because the subgroup of nonseminoma patients was small, resulting in imprecise effect estimates. In their registry-based prevalence case-control study, Davies et al (6) found that the RR per 1/4 pint of milk per day (i.e., f120 mL per day) at age 17 years was 1.39 (95% CI, 1.19-1.63).…”
Section: Discussioncontrasting
confidence: 56%
“…Mortality risk from TC reaches its peak between ages 20 and 34 and drops to a stabilization of rates near the age of 40 (age effect), as it has been observed in previous studies in Western and Eastern European countries [2]. The increased incidence risk of testicular cancer was detected for men 15-44 in most industrialized countries [2,[28][29][30][31][32]. Spain has noted recently the most rapid inclines in TC incidence among European countries, although it has one of the lowest TC incidence and mortality rates in Europe [1,2].…”
Section: Discussionsupporting
confidence: 56%
“…Testicular cancer incidence is much lower in Finland than in Denmark and the other Nordic countries (10). Furthermore, testicular cancer incidence is higher among the white than the black population in the USA (29,30). This suggests that genetic factors have an impact on testicular function.…”
Section: Discussionmentioning
confidence: 99%